(untitled) (Innovative professional education, 2025)
The article examines the effectiveness of using the Heyzine platform to create interactive flipbooks to improve the learning process. The advantages of using flipbooks in teaching, the ease of creating them on the Heyzine platform, and some areas of application in various educational contexts are considered. Particular attention is paid to the impact of flipbooks on student interest and motivation, as well as their importance for organizing distance learning and economic resources. The work emphasizes that Heyzine is an effective tool for creating modern and interesting educational materials that contribute to improving the quality of education.